2018
DOI: 10.1039/c7ra13506h
|View full text |Cite
|
Sign up to set email alerts
|

High-performance piezoelectric energy harvesting of vertically aligned Pb(Zr,Ti)O3 nanorod arrays

Abstract: Recent developments of self-powered devices and systems have attracted much attention. Lead zirconate titanate (PZT) has been regarded as one of the most promising materials for building high-performance nanogenerators. Herein, vertically aligned PZT nanorod arrays were synthesized on a pre-oxidized Ti substrate in the presence of a surfactant by a one-step hydrothermal method. The PZT nanorod arrays consist of an initial layer of a PZT film and well aligned nanorods with (001) respectively. Moreover, the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…The changes in crystallinity were shown to increase the dielectric constant (ε′ ~109.6) and energy density (U e ~21.7 J/cm 3 ) with a breakdown strength (E b ) of 3.81×10 3 kV/cm compared to pristine PVDF (ε′ ~11. 6 and U e ~2.16 J/cm 3 at 3.98 × 10 3 kV/cm).…”
Section: Barium Titanate (Batio 3 Bt)mentioning
confidence: 94%
See 1 more Smart Citation
“…The changes in crystallinity were shown to increase the dielectric constant (ε′ ~109.6) and energy density (U e ~21.7 J/cm 3 ) with a breakdown strength (E b ) of 3.81×10 3 kV/cm compared to pristine PVDF (ε′ ~11. 6 and U e ~2.16 J/cm 3 at 3.98 × 10 3 kV/cm).…”
Section: Barium Titanate (Batio 3 Bt)mentioning
confidence: 94%
“…A piezoelectric energy harvester was fabricated based on the PZT NR arrays and exhibited an outstanding energy harvesting performance with opencircuit output voltages of 3.3 V and 8 V when subjected to a compressive 10 N force and a finger tapping motion, respectively. Moreover, the average power densities generated under these two mechanical stimuli were up to 3.16 and 5.92 µW cm -2 with an external load of 1 M [6]. Pbbased materials are still being prepared and investigated for energy-harvesting applications [7], including hybrids such as 30 vol% PMN-PT/CNT/PVDF [8].…”
Section: Introductionmentioning
confidence: 99%
“…The noticeable piezoelectric nanostructures, such as NWs, nanofibers, and nanobelts, by utilizing inorganic materials of PZT, PMN-PT, ZnO, BaTiO 3 , and ferroelectric polymer of PVDF and its copolymer P(VDF-TrFE), have shown remarkable ability to harvest energy from small mechanical movements and gain higher energy conversion efficiency as compared to their micro-and macro-sized counterparts, which was attributed to size-effects, enhanced properties, and improved mechanical flexibility. 103,104,[189][190][191][192][193][194][195][196][197][198][199] Various methods are used for the synthesis of nanostructures, such as CVD, physical vapor deposition (PVD), molecular beam epitaxy (MBE), PLD, hydrothermal and chemical synthesis, and electrospinning.…”
Section: Nano-fabrication Processmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] In the past, many authors, including our group have reported lead-based materials for suitable pressure sensors in the low and high-pressure range, where a signicant change in dielectric constant, piezoelectric coefficient and capacitive reactance was observed as a function of pressure. [1][2][3][5][6][7]13,[18][19][20][21][22][23][24][25][26] However, the effect of pressure on change in dielectric constant was not as signicant that it can be realized for real high-pressure sensor devices. Another drawback was the linearity in dielectric constant as a function of pressure.…”
Section: Introductionmentioning
confidence: 99%